The Function of Emotions When and Why Emotions Help Us (Springer International Publishing, 2018)
This eye-opening text brings together research from behavioral science, neuroscience, and other fields to make a cogent case for emotions acting as a practical framework for living our lives. A dozen basic emotions are analyzed in terms of what causes them, how they change thoughts and behaviors, and the functional value of these responses. Contrary to the common idea of emotions as fleeting occurrences, they are shown as having the potential for lasting impact on moods, thoughts, and behaviors. Intriguing findings assert that even negative emotions such as jealousy and anger can have positive results such as promoting positive goals, and can lead to successful outcomes in overarching domains such as cognition and well-being. Among the topics covered: · How fear and anxiety promote attention and protective behavior. · How sadness and depression promote analysis of complex problems in goal-pursuits. · How happiness promotes processing and attention. · How love promotes relationship development and goal attainment. · How pride promotes sense of self and identity. The Function of Emotions is a valuable resource for students, researchers, and clinicians interested in the psychology and neuroscience of emotions and their function in everyday life. It will attract an interested readership among professionals working in such fields as education, management and leadership, social work, and psychotherapy.